Parte subjetivamente compleja, indivisibilidad y anulabilidad por incapacidad relativa: la norma más oscura del código civil también cumple treinta años (¿y dice adiós?) - León Hilario, Leysser L. (2014)
The Peruvian Civil Code commemorates its thirty years of existence. Some of its rules’content is clear, while some other rules are –in the words of the author– dark andquestionable.  One of these controversial rules in its meaning and application is that contained in article 226 of the Code, relatedwith a person’s legal capacity.In this article, the author makes a historical and comparative analysis of such article, to then approach the problems contained in it, contrasting their role in the current social reality and verifying if such figure is still useful in our legal system.